Epidermal Cyst Instead of Baker’s Cyst in the Popliteal Fossa: A Case Report and Literature Review - Alansari AH; Beshr MS (International Medical Case Reports Journal, 2025)
Arowa H Alansari,1,* Mohammed S Beshr2,* 1Faculty of Medicine, Gharyan University, Gharyan, Libya; 2Faculty of Medicine and Health Sciences, Sana’a University, Sana’a, Yemen*These authors contributed equally to this workCorrespondence: Mohammed S Beshr, Faculty of Medicine and Health Sciences, Sana’a University, Sana’a, Yemen, Tel +967 770771741, Email mbeshr2020@gmail.comBackground: Epidermal cysts are usually found in the head, neck, and trunk, and they are very rare to be found in the popliteal fossa. Baker’s cyst is the most common cause of popliteal fossa swelling. To our knowledge, this is the seventh reported case of an epidermal inclusion cyst in the knee area.Case Presentation: A 39-year-old male presented with popliteal swelling that had been present since 2016. It was not associated with pain or restriction of movement. On examination, the swelling was firm, well-capsulated, freely mobile, and not fixed to the underlying structure. There was no tenderness, warmth, or any signs of inflammation. The MRI revealed a 1.5× 3 cm circumscribed subcutaneous lesion with low T1 and intermediate T2W signal, with normal adjacent joint structures. A total excision was performed, and the pathology report confirmed the diagnosis of epidermal inclusion cyst.Conclusion: Popliteal fossa masses are commonly due to Baker’s cysts. Other pathologies should be considered when the presentation is atypical, unclear, or not supported by imaging. Our literature search highlighted the rare occurrence of epidermal cysts around the knee joint. Long-standing asymptomatic popliteal swellings that are either stable or progressive should raise suspicion of alternative pathologies.Keywords: epidermal cyst, inclusion cyst, popliteal fossa, Baker’s cyst, popliteal swelling